Effect of Organic Manures and Biofertilizers on Growth and Yield of Rheum Australe D. Don. Cultivated in Himachal Himalaya - Bhardwaj, Ravi; Sood, Meenu (Indian Forester, 2014)
Rheum australeWall ex Meissn. a perennial herb, is distributed in the Himalayas from Kashmir to Sikkim at altitude of 2800-5200 m. In Himachal Pradesh it is found growing in Chhota Bhangal and Bara Bhangal of Kangra; Pangi Bharmour of Chamba, Parvati Valley of Kullu, Dodra kwar, Khashadhar and Rohru ranges of Shimla district, Kinnaur and Lahaul Spiti districts. Population density is between 0.5 and 1.5 plant square meter in very restricted localities and is designated as endangered in status. The experiment on Rheum australe was conducted to determine the effect of different organic manures , biofertilizers and NPK on growth and yield of Rheum australeand also to work out its cost of cultivation to standardize the cultivation technology. The results showed that maximum plant height, above ground biomass ,underground biomass and underground biomass yield was recorded maximum using NPK (120:60:30 kg/ ha) and which was followed by Vermicompost + Azotobacter+ PSB (10t:5kg:5kg) and minimum was recorded in control. Benefit-cost ratio of 10.15 was observed maximum when NPK @ (120 : 60: 30 Kg/ha) was applied, which was followed by treatment F where FYM + Azotobacter + PSB (10t : 5kg :5kg) with a BCR of 8.09.